2015
DOI: 10.1007/s00441-015-2118-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the NLRP3/caspase-1 inflammasome in human dental pulp tissue and human dental pulp fibroblasts

Abstract: The NLRP3/caspase-1 inflammasome pathway plays an important role in cellular immune defence against bacterial infection; however, its function in human dental pulp tissue and human dental pulp fibroblasts remains poorly understood. We demonstrate that NLRP3 protein expression occurs to a greater extent in pulp tissue with irreversible pulpitis than in normal pulp tissue and in tissue with reversible pulpitis. Caspase-1 is present in its active (cleaved) form only in pulp tissue with irreversible pulpitis. NLRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 45 publications
5
67
0
Order By: Relevance
“…One microgram of total RNA was used as a template to synthesise first-strand complementary DNA using oligo-dT priming with the Omniscript RT kit (Qiagen, USA). QPCR were performed with SYBR Green PCR master mix reagent (Takara, Japan) in an ABI Prism 7500 qPCR system (Advanced Biosystems, USA) as previously described3. The human gene-specific primers for cDNA can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One microgram of total RNA was used as a template to synthesise first-strand complementary DNA using oligo-dT priming with the Omniscript RT kit (Qiagen, USA). QPCR were performed with SYBR Green PCR master mix reagent (Takara, Japan) in an ABI Prism 7500 qPCR system (Advanced Biosystems, USA) as previously described3. The human gene-specific primers for cDNA can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Pulpitis is an inflammatory disease which occurs when the infection of caries-related microorganisms penetrates the dentinal tubules and into the pulpal tissue2. During the inflammatory phase, the pulp tissue reacts to bacterial irritants via innate and/or adaptive immune responses, thus releasing a range of chemokines and pro-inflammatory cytokines3. Inflammation and regeneration in dental pulp tissue can appear to be contradictory processes, however, they are clearly inter-related4.…”
mentioning
confidence: 99%
“…On the other hand, recent studies revealed the importance of the TLR-inflammasome axis in pulpal and periapical inflammatory response [171, 172]. Although macrophage-derived IL-1 is the central mediator in the development of periapical lesions [72, 141], an increased number of NALP3 positive cells, including an influx of myeloids, was quite apparent with the progression of periapical inflammation[172].…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Periapical mentioning
confidence: 99%
“…Belonging to the Nod-like receptor family, NLRP3 has emerged as the most versatile innate immune receptor because of its broad specificity. 18 Several studies have reported that a broad array of stimuli can activate the NLRP3-CASP1 inflammasome pathway and release of the proinflammatory factor IL1B in immune cells, which is involved in innate immune responses. However, whether Mn, a naturally occurring heavy metal, is involved in the innate immune response through the NLRP3-CASP1 inflammasome pathway in the microglia has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%